2013
DOI: 10.1002/jcc.23515
|View full text |Cite
|
Sign up to set email alerts
|

Is the DPT tautomerization of the long A·G Watson–Crick DNA base mispair a source of the adenine and guanine mutagenic tautomers? A QM and QTAIM response to the biologically important question

Abstract: Herein, we first address the question posed in the title by establishing the tautomerization trajectory via the double proton transfer of the adenine·guanine (A·G) DNA base mispair formed by the canonical tautomers of the A and G bases into the A*·G* DNA base mispair, involving mutagenic tautomers, with the use of the quantum-mechanical calculations and quantum theory of atoms in molecules (QTAIM). It was detected that the A·G ↔ A*·G* tautomerization proceeds through the asynchronous concerted mechanism. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(30 citation statements)
references
References 136 publications
0
29
1
Order By: Relevance
“…Purinergic Signalling (2017) 13: [1][2][3][4][5][6][7][8][9][10][11][12]by activating the ERK1/2 and PI3K/AKT pathways [64]. It was demonstrated that P2X7 receptor activation enhances invasiveness through a mechanism involving Ca 2+ -activated SK3 K + -channel activity in the mammary carcinoma cell line MDA-MB-435 s [65].…”
Section: Adora2amentioning
confidence: 99%
See 2 more Smart Citations
“…Purinergic Signalling (2017) 13: [1][2][3][4][5][6][7][8][9][10][11][12]by activating the ERK1/2 and PI3K/AKT pathways [64]. It was demonstrated that P2X7 receptor activation enhances invasiveness through a mechanism involving Ca 2+ -activated SK3 K + -channel activity in the mammary carcinoma cell line MDA-MB-435 s [65].…”
Section: Adora2amentioning
confidence: 99%
“…Purine molecules, such as adenine and guanine, are components of the genetic material (DNA and RNA) of all living beings. Purine and pyrimidine tautomeric equilibria in nucleic acids was postulated to be significant in events such as DNA replication and repair as well as in the occurrence of point mutations [8].As nucleosides and nucleotides, purines play other highly strategic roles, acting as energy intermediates, allosteric regulators of key metabolic activities, redox molecules, and chemical messengers for signal transduction events. The two most important purines serving as extracellular ligands for paracrine and autocrine signaling are ATP and its dephosphorylated form, adenosine (ADO).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Bader's quantum theory of Atoms in Molecules (QTAIM), using program package AIMAll, was applied to analyze the electron density distribution. The presence of the bond critical point (BCP), namely the so‐called (3,−1) BCP, and a bond path between hydrogen donor and acceptor, as well as the positive value of the Laplacian at this BCP (Δ ρ > 0), were considered as criteria for the H‐bond formation . Wave functions were obtained at the level of theory used for geometry optimization.…”
Section: Methodsmentioning
confidence: 99%
“…It was established for sure that generally accepted mechanism of the double proton transfer (DPT) along intermolecular H-bonds in the Watson-Crick (WC) (so-called Löwdin's mechanism), [24][25][26][27][28][29] wobble (w) base pairs, 30,31 biologically important A$G, 32 A$C*, 33 G*$T, 34 C$T, 35 G$G * syn , 36 A*$A syn , 37 A*$G * syn , 38 H$C, 39,40 H$H 39,40 and H$A 39,42 base mispairs and also in the protein-DNA complexes 26,43,44 can't be considered as the source of the mutagenic tautomers formations due to the dynamical instability of the terminal complexes containing mutagenic tautomers of the DNA bases. [26][27][28][29][31][32][33][34][35][36][37][38][39][40][41][42]44 For the rst time, we have proposed a novel theoretical approach to the elucidation of the microstructural mechanisms of the incorporation and replication errors arising at the DNA replication due to the intrinsic ability of the purine$pyrimidine (A$T, G$C, G$T and A$C), purine$purine (A$A and G$G) and pyrimidine$pyrimidine (C$C and T$T) DNA base mispairs to perform WC 4 w tautomeric transitions via the sequential proton transfer (PT). [45]…”
Section: Introductionmentioning
confidence: 99%